2016
DOI: 10.3390/ijms17111860
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase-Dependent Role of the Soluble Form of Neurotensin Receptor-3/Sortilin in Colorectal Cancer Cell Dissociation

Abstract: The aim of the present review is to unravel the mechanisms of action of the soluble form of the neurotensin (NT) receptor-3 (NTSR3), also called Sortilin, in numerous physiopathological processes including cancer development, cardiovascular diseases and depression. Sortilin/NTSR3 is a transmembrane protein thought to exert multiple functions both intracellularly and at the level of the plasma membrane. The Sortilin/NTSR3 extracellular domain is released by shedding from all the cells expressing the protein. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Previous studies reported that serum sortilin levels are associated with cardiovascular risk, such as aortic calcification ( 31 ) and atherothrombosis ( 32 ), as well as depression ( 33 ). Soluble sortilin can also activate survival pathways in cancer cells ( 6 , 34 ). Therefore, it is important to understand whether soluble sortilin contributes to diseases through the formation of monomers and/or homodimers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that serum sortilin levels are associated with cardiovascular risk, such as aortic calcification ( 31 ) and atherothrombosis ( 32 ), as well as depression ( 33 ). Soluble sortilin can also activate survival pathways in cancer cells ( 6 , 34 ). Therefore, it is important to understand whether soluble sortilin contributes to diseases through the formation of monomers and/or homodimers.…”
Section: Resultsmentioning
confidence: 99%
“…Sortilin, which is ubiquitously expressed and essential for proper function of many tissues and cell types, is a sorting receptor that directs target proteins, including growth factors, signaling receptors, and enzymes, to their destined location in the secretory or endocytic compartments of cells ( 4 ). Sortilin has conversely also emerged as a major cause of malignancies in a range of diseases ( 5 ), including cancer ( 6 9 ), type 2 diabetes mellitus ( 10 ), hypercholesterolemia ( 11 13 ), atherosclerosis ( 14 , 15 ), and neurodegenerative disorders ( 16 , 17 ), such as Alzheimer's disease ( 18 , 19 ). The atypical increase in intracellular trafficking by sortilin and its subsequent lysosomal degradation ( 16 ) or secretion ( 11 , 15 ) have been linked to the pathogenesis of the aforementioned diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The FAK signaling pathway can integrate multiple extracellular signals to regulate the expression of downstream molecules, thereby controlling the proliferation and apoptosis of cells. This pathway is cascaded with multiple signal transduction pathways in the body and is the central link of intracellular and extracellular signal transduction [14,15].. A large number of studies have confirmed that the abnormal activation of FAK signaling pathway is closely related to the occurrence and development of various malignant tumors [16][17][18]. In the study of pancreatic cancer, Gao Z et al [19] reported that the overexpression of SRPX2 (Sushi repeat-containing protein, X-linked 2), which is dependent on the phosphorylation level of FAK, is closely related to the local invasion and distant metastasis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15]. A large number of studies have confirmed that the abnormal activation of FAK signaling pathway is closely related to the occurrence and development of various malignant tumors [16][17][18].…”
Section: Real-time Pcr Verificationmentioning
confidence: 97%